Commonwealth banking systems - Crick, W. F.; Sayers, R. S. (Oxford, Clarendon Press, 1965)
The book covers banking in every part of the Commonwealth , excluding United Kingdom and including South Africa which at the time of writing this book was no longer part of the Commonwealth.
Successor to Banking in the British Commonwealth, edited by R.S. Sayers.
Includes bibliographical footnotes.
oif 04/03/2019
Loans
Keywords: Banks and banking